Influence of seascape spatial pattern on the trophic niche of an omnivorous fish. Issue 2 (9th February 2022) - Santos, Rolando O.; James, W. Ryan; Nelson, James A.; Rehage, Jennifer S.; Serafy, Joseph; Pittman, Simon J.; Lirman, Diego
Abstract: Habitat fragmentation of submerged aquatic vegetation (SAV) transforms the spatial pattern of seascapes by changing both the total area and spatial configuration of the habitat patches. The ecological effects of SAV seascapes are most often assessed using metrics of biological community composition (e.g., species and assemblage changes). We know considerably less about the effects of seascape structure on ecological processes such as food web function and energy flow. Here, we assess the difference in the trophic niche of Pinfish ( Lagodon rhomboides, a generalist omnivore) across a spatial gradient of SAV from continuous to highly fragmented seascapes in Biscayne Bay (Miami, Florida, USA). The Bay seascapes are influenced by freshwater management practices that alter the distribution of SAV habitat and fish species abundance, diversity, and community assemblage. We combined SAV seascape maps with stable isotope and hypervolume analyses to determine how trophic niche size and overlap varied with changes in the seascape. We observed similar resource use across the seascape, but trophic niche size increased in more fragmented SAV seascapes, suggesting diversification of trophic roles and energy flow pathways. Pinfish collected from more continuous SAV habitats had smaller trophic niche size and higher trophic levels. Both trophic response metrics manifested a threshold response that depended on distinct SAV spatial characteristics (amount vs. spatial configuration) and environmental conditions. Our results suggest that habitat fragmentation of SAV seascape structure has ecological implications that could affect energy flow with cascading consequences for food web stability and ecosystem functioning.